Retail banking activities of City Bank Ltd. Gulshan branch of the year 2009, Dhaka - Islam, Md. Mozahidul (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2009.